Ethnobotanical study of medicinal plants used by the Kenyah community of Borneo - Sundara Rajoo, Keeren; Lepun, Philip; Alan, Ribka; Karam, Daljit Singh; Abdu, Arifin; Rosli, Zamri; Norul Izani; James Gerusu, Geoffery (Elsevier, 2022)
Ethnopharmacological relevance: Sarawak is located in one of the world's most biodiverse regions and is home to more than 40 sub-ethnic groups that each have their own distinct culture, language and lifestyle. This has given rise to numerous, unique ethnobotanical systems. However, due to rapid urbanization, this traditional knowledge is at a risk of extinction. Yet, ethnobotanical studies in Sarawak are almost non-existent, especially among Orang Ulu communities like the Kenyah. Aim of study: Therefore, this study was conducted to document the ethnomedicinal knowledge of the Kenyah community. The main objectives of this study are: 1) To determine and document the diversity of medicinal plants used by the Kenyah community, 2) To determine whether the availability of modern medicine has affected Kenyah traditional medicine, and 3) To identify plants which have not been previously cited or used for previously unreported medical uses. Materials and methods: We conducted repeated interviews and field surveys at the Asap-Koyan Resettlement Area, Belaga Sarawak. A total of 24 respondents from four Kenyah longhouses were interviewed in this study. Individuals possessing extensive traditional medicinal knowledge were identified via preliminary interviews or by viva voce. Translators were employed to ensure that there was no miscommunication. The results were evaluated based on the plant's total use-reports and number of respondents citing the plant. The data was also evaluated based on use-reports by ailment category. Results: Over 95% of the respondents were 40 years and older (58.21 years old ± 11.21). This was due to the younger members of the community (40 years old and below) admitting that they had almost no knowledge regarding traditional medicine, as they preferred relying on modern medicine. A total of 61 plant species were mentioned by the 24 respondents Seven plants had five or more respondents citing it, which was more than 20% of the respondents. These plants were Piper betle, Homalomena cordata, Senna alata, Annona muricata, Derris elliptica, Blumea balsamifera and Coscinium fenestratum. Conclusion: Almost all of the cited plants had been previously recorded to be used in either Ayurvedic, Chinese herbal medicine, Malay traditional medicine or other Asian ethnomedicinal systems. However, there were four highly cited species that were used for treatments that were scarcely reported in past literature. These were piper betle (used by Kenyah to treat fever), Sauropus andrognus (used by Kenyah to treat fever), Derris elliptica (used by Kenyah to treat fever and influenza) and Coscinuim fenestratum (used by Kenyah to treat toxic effects from non-medical substances).